2017
DOI: 10.1016/j.neures.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent proteolytic cleavage of cell adhesion molecules regulates excitatory synaptic development and function

Abstract: Activity-dependent remodeling of neuronal connections is critical to nervous system development and function. These processes rely on the ability of synapses to detect neuronal activity and translate it into the appropriate molecular signals. One way to convert neuronal activity into downstream signaling is the proteolytic cleavage of cell adhesion molecules (CAMs). Here we review studies demonstrating the mechanisms by which proteolytic processing of CAMs direct the structural and functional remodeling of exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 87 publications
0
25
0
Order By: Relevance
“…Similarly, in a recent analysis of differential gene expression profiles in neurons from twins with treatment-resistant SCZ who had discordant responses to clozapine using pluripotent stem (iPS) cell based technology, we found that differentially expressed genes were enriched for “cell adhesion” and “biological adhesion” [6]. Cell adhesion is essential for forming tissue and neuronal connections crucial for nervous system development [31]. Animal studies suggest that dysfunction of neuronal cell adhesion molecules, which are expressed primarily in the central nervous system where they regulate synaptic signaling, may lead to impairment of memory and learning [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a recent analysis of differential gene expression profiles in neurons from twins with treatment-resistant SCZ who had discordant responses to clozapine using pluripotent stem (iPS) cell based technology, we found that differentially expressed genes were enriched for “cell adhesion” and “biological adhesion” [6]. Cell adhesion is essential for forming tissue and neuronal connections crucial for nervous system development [31]. Animal studies suggest that dysfunction of neuronal cell adhesion molecules, which are expressed primarily in the central nervous system where they regulate synaptic signaling, may lead to impairment of memory and learning [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…This particular enrichment of proteases reflects the fact that glycosylation, and probably sialylation 57 , is important for protease activity 58 . For ADAMs, it is known that their enzymatic activity depends on their glycosylation and they perform activity-dependent proteolysis of synaptic cell adhesion molecules such as neuroligin-1 [59][60][61][62] . Further studies investigating the impact of sialic acids on specific N-linked glycans in ADAM proteases in synaptosomes might be of high interest to shed light on their involvement in synaptic transmission and learning and memory related processes.…”
Section: Overview Of the Synaptic Proteome And Sialiomementioning
confidence: 99%
“…Active neuropsin cleaves the extracellular domain of L1CAM and produce a neuropsin specific 180 kDa fragment [21,28] (depicted in Figure 4). The function of this neuropsin specific L1CAM fragment has not been investigated yet, but the role of cell adhesion molecules in synaptic plasticity [29][30][31][32] suggests that neuropsin-specific L1CAM cleavage decreases synaptic adhesion and subsequent increases the flexibility of synaptic structures. Neuropsin is involved in the synaptogenesis of L1CAM expressing orphan and small synaptic boutons in pre-synaptic membranes of the Schaffer-collateral pathway in the hippocampal CA1 substructure [28].…”
Section: The Neurobiology Of Neuropsinmentioning
confidence: 99%